Enantioselective cytotoxicity of ZnS:Mn quantum dots in A549 cells. Issue 8 (13th June 2017) - Kuznetsova, V.A.; Visheratina, A.K.; Ryan, A.; Martynenko, I.V.; Loudon, A.; Maguire, C.M.; Purcell‐Milton, F.; Orlova, A.O.; Baranov, A.V.; Fedorov, A.V.; Prina‐Mello, A.; Volkov, Y.; et al.
Abstract: Chirality strongly influences many biological properties of materials, such as cell accumulation, enzymatic activity, and toxicity. In the past decade, it has been shown that quantum dots (QDs), fluorescent semiconductor nanoparticles with unique optical properties, can demonstrate optical activity due to chiral ligands bound on their surface. Optically active QDs could find potential applications in biomedical research, therapy, and diagnostics. Consequently, it is very important to investigate the interaction of QDs capped with chiral ligands with living cells. The aim of our study was to investigate the influence of the induced chirality of Mn‐doped ZnS QDs on the viability of A549 cells. These QDs were stabilized with D‐ and L‐cysteine using a ligand exchange technique. The optical properties of QDs were studied using UV–Vis, photoluminescence (PL), and circular dichroism (CD) spectroscopy. The cytotoxicity of QDs was investigated by high content screening analysis. It was found that QDs stabilized by opposite ligand enantiomers, had identical PL and UV–Vis spectra and mirror‐imaged CD spectra, but displayed different cytotoxicity: QDs capped with D‐cysteine had greater cytotoxicity than L‐cysteine capped QDs. Abstract :